2020
DOI: 10.3389/fmats.2020.00276
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanoarchitectonics: A New Material Horizon for Reinforcement of Sustainable Polymers

Abstract: Using nanoscience to solve the issues that limit the development of a sustainable society is one of the most important topics at present. Sustainable polymers play an important role in the construction of a sustainable society, but its large-scale application is usually limited by the poor mechanical and shape-memory properties of the commonly used epoxy resin. The utilization of nanoarchitectures to improve the shape-memory performance of composite materials is an effective approach. Graphene, among the used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…On the other hand, GO nanostructures can be employed as nanofillers to strengthen mechanical properties of polymers [24] and can be used to fabricate artificial tough nacre of interest in aerospace applications [25,26]. Additionally, GO can endow with shape memory behavior to nanocomposites [27,28] for bone repair with minimal invasive surgery [29], and electrical actuators with low power consumption [30], essential for many applications in bioengineering. Recently, first-principle calculations have shown that GO with highly ordered epoxy groups can experience shape memory effect on its own without the presence of a polymer matrix [31,32] and can experience recoverable strain rates up to 14%.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, GO nanostructures can be employed as nanofillers to strengthen mechanical properties of polymers [24] and can be used to fabricate artificial tough nacre of interest in aerospace applications [25,26]. Additionally, GO can endow with shape memory behavior to nanocomposites [27,28] for bone repair with minimal invasive surgery [29], and electrical actuators with low power consumption [30], essential for many applications in bioengineering. Recently, first-principle calculations have shown that GO with highly ordered epoxy groups can experience shape memory effect on its own without the presence of a polymer matrix [31,32] and can experience recoverable strain rates up to 14%.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoarchitectonics methodology is supposed to produce functional materials and functional structures from nanoscale unit components through the combination and selection of various processes, including organic synthesis (especially heteromolecular synthesis), atom/molecular manipulation, materials synthesis, self-assembly/self-organization, field-assisted assembly, microfabrication, and bio-related processes [ 35 , 36 ]. Because these features can be applied to many kinds of materials, nanoarchitectonics strategies have been generally used for production of functional materials [ 37 , 38 , 39 ] and regulation of fine structures [ 40 , 41 , 42 ]. Not limited to material synthesis and fabrication, the nanoarchitectonics concept has been widely applied to various application-oriented fields such as catalysts [ 43 , 44 , 45 ], sensors [ 46 , 47 , 48 ], devices [ 49 , 50 , 51 ], energy-related applications [ 52 , 53 , 54 ], environmental applications [ 55 , 56 , 57 ], bio-related functions [ 58 , 59 , 60 ], and biomedical applications [ 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%